Species-dependent differences of embryonic stem cell-derived neural stem cells after Interferon gamma treatment - Walter, Janine; Dihné, Marcel (Frontiers in Cellular Neuroscience, 2012)
Abstract Pluripotent stem cell (pSC)-derived, neural stem cells (NSCs) are actually extensively explored in the field of neuroregeneration and to clarify disease mechanisms or model neurological diseases in vitro. Regarding the latter, proliferation and differentiation of pSC-derived NSCs are investigated under the influence of a variety of different substances among them key players of inflammation. However, results generated on a murine genetic background are not always representative for the human situation which increasingly leads to the application of human cell culture systems derived from human pSCs. We investigated here, if the recently described interferon gamma (IFNɣ)-induced dysregulated neural phenotype characterized by simultaneous expression of glial and neuronal markers on murine NSCs [1,2] can also be found on a human genetic background. For this purpose, we performed experiments with human embryonic stem cell-derived NSCs. We could show that the IFNɣ-induced dysregulated neural phenotype cannot be induced in human NSCs. This difference occurs, although typical genes like signal transducers and activators of transcription 1 (Stat 1) or interferon regulatory factor 9 (IRF-9) are similarly regulated by IFNɣin both, murine and human populations. These results illustrate that fundamental differences between murine and human neural populations exist in vitro, independent of anatomical system-related properties.